TikTok practices among teenagers in Portugal: a uses & gratifications approach - Dias, Patrícia (2022)
TikTok is consolidating its place in the social media landscape. During the first three months of the COVID-19, it was the most downloaded app worldwide, and it gained 500,000 new users in Portugal. Our study sets out to map the practices of Portuguese teenagers (10–16) on TikTok. Using a Uses and Gratifications approach (U&G), we conducted an online survey with a non-probabilistic sample of 347 TikTok users. Our findings show relevant differences between younger (10–12) and older (13–16) teenagers. The youngest are more careful about privacy and enjoy more experimentation as content creators, while the oldest are more focused on building an audience. Entertainment and self-expression are the main motivations for using the platform. About 50% of our sample admits at least one behavior that is indicative of addiction.